The influence of the amount of carbon in steels on the physicomechanical characteristics of surface layers during hardening by high-speed friction - Kapral, Yu.R.; Pobereyko, B.P.; Dufanets, S.M.; Divchur, Yu.V.; Kuhar, R.O. (Forestry, Forest, Paper and Woodworking Industry, 2019)
Steels C10, C20, C45, 66Mn4 and C80W1 in the normalized state were used to research the influence of the amount of carbon on the process of hardening by high-speed friction. This method refers to thermo-mechanical methods of hardening so the amount of carbon in the steel plays an important role in the formation of hardened layers. Several studies indicate that steels are hardened with a carbon content of more than 0.3%. We have shown that hardened layers can be obtained even on steels with a carbon content of 0.1% by the method of hardening with a hinged tool-disk regarding the workpiece. In this way, on steel C10 the strengthened layers in the thickness of 0,5 mm and microhardness of 7 GPa are received. Similar results were obtained on steel C20. On steel C45 a reinforced layer with a thickness of 0.9 mm with a microhardness of more than 10 GPa was obtained, and on steel 66Mn4, the thickness of the reinforced layer with a microhardness of 11 GPa is 1.1 mm. On C80W1 tool steel the microhardness of the hardened layer of 14 GPa is observed at a depth of up to 0.9 mm, and at a depth of 1.1 mm it decreases to 10 GPa. Also steel 66Mn4 and C80W1 an increase of microhardness up to 5...6 GPa is observed at a depth of 1.4 mm. Reinforcement of steel C10 and steel C20 by high-speed friction can be used to improve the physicomechanical and tribological performance of elements of technological equipment. Physicomechanical properties of hardened layers obtained on structural steels with a carbon content of more than 0.4% are close to the characteristics of tool steels that allow the use of steel C45 and 66Mn4 for the manufacture of wood cutting tools, and hardening steel C80W1 allows to replace the volume hardening at the time operation tool making.